TPACK Implementation for Teaching Reading Skills in ELT at SMKN 1 Percut Sei Tuan - Lubis, Winny Meilita; Manullang , Hari Mukti; Maulidea Karimah; Meisuri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This study aims to examine the implementation of the TPACK (Technological Pedagogical Content Knowledge) framework in teaching reading skills within an English Language Teaching (ELT) context at SMKN 1 Percut Sei Tuan. The research explores how the teacher facilitates the reading learning activity in ELT using technology. A qualitative approach was employed, using classroom observations, teacher interviews, and video recordings to gather data. The findings reveal that the teacher utilized e-books, online dictionaries, and group chats effectively to support learning. These tools provided accessible materials and encouraged collaboration, improving students’ engagement and comprehension. Pedagogical strategies, such as guiding students through analytical exposition texts and employing 5W+1H questioning, helped develop critical reading skills. The teacher connected reading activities to real-world issues, making lessons relevant and engaging. Despite these strengths, the study identified areas for improvement. Limited use of multimedia and the lack of vocationally specific content reduced the alignment of lessons with students’ professional interests. Additionally, low motivation among students and challenges with digital literacy hindered the optimal use of technology. The study concludes that while TPACK supports teaching reading skills, incorporating advanced technologies and vocationally relevant materials is essential for improving engagement and learning outcomes in vocational education.